Comparative Analysis of Agriculture Curriculum with Agronomy Concentration in Vocational High Schools in Germany and Indonesia - Astuti, Widya Puji; Susilana, Rudi; Johan, Riche Cynthia (Jurnal Educative: Journal of Educational Studies, 2024)
The German vocational education system has developed steadily over centuries and is recognized as a global reference in providing vocational education. This study compares the agricultural curriculum with agronomy concentration in vocational high schools in Indonesia with the vocational education system in Germany. The study is expected to be able to offer strategic recommendations for the development of agricultural vocational education in Indonesia, provide strategic insights for the development of a more relevant agricultural vocational high school curriculum, and be able to create promising career opportunities in agriculture. This study uses a qualitative approach with a content analysis design on the documents that are the primary analysis sources. The results show that Germany excels in integrating theory, practice, technology, and industry involvement through an intensive Duale Ausbildung system. The longer duration of education and the use of advanced technologies such as smart farming make Germany more prepared to face the industrial era 4.0. In contrast, Indonesia is starting to move towards innovation with a project-based learning approach, but industry involvement and recognition of competency certification are still limited. The study's conclusion shows that although the Indonesian agronomy curriculum has approached international standards, strengthening industrial partnerships, modern technology, and global certification recognition need to be improved to increase the competitiveness of graduates in the global market.